Training Enhancing the Potential of Integrated Gardens to Support Family Food and Nutritional Independence - Titik Juwariyah; Dewi Retno Puspitosari; Ary Kristijono; Diyan Wahyuningsih; Edi Santoso; Rizki Bahtiyar Ardyansah (STIKes Patria Husada Blitar, 2026)
Introduction: The elderly are a vulnerable age group socially, economically, and health-wise, especially in rural and suburban areas. Based on data from the Ministry of Social Affairs of the Republic of Indonesia, approximately 40% of the total 25.67 million elderly in Indonesia are in the lowest socioeconomic status, which is categorized as vulnerable and potentially experiencing various physical and psychological problems. Methods: This community service activity carries the theme